Maxillofacial Fracture Trauma: Orbital Walls Fracture And Their Association Using Multilayer Neural Network Perspectives - Wan Muhamad Amir W Ahmad; Ramizu Shaari; Nor Farid Mohd Noor; Mohamad Nasarudin Adnan; Nurul Asyikin Nizam Akbar; Nor Azlida Aleng; Farah Muna Mohamad Ghazali; Nurfadhlina Abdul Halim; Mohamad Shafiq Mohd Ibrahim; Nurul Husna Mustapa; Muhammad Azeem Yaqoob (publishoa, 2024)
Non-Indexed Publication